SCIENTIFIC-THEORETICAL AND LEGAL FOUNDATIONS OF INCLUSIVE EDUCATION - Khujayarova Nafisa Sultanmurodovna (Scholars Digest Publishing, 2025)
The article describes the scientific-theoretical and legal foundations of inclusive education, the education and education of children with disabilities and their adaptation to social life, the study of pedagogical-psychological characteristics in teaching them, the identification of problems, the justification of aspects of effectiveness.
Keywords: Inclusive education, pedagogical-psychological characteristics, scientific-theoretical foundations, purpose, objectives of inclusive education.